ANALISIS PHYTOLITH DAN STARCH UNTUK STUDI ARKEOLOGI LINGKUNGAN - Alifah Alifah (Pusat Penelitian Arkeologi Nasional, 2017)
Environmental issues in archaeology have become a very interesting theme to be researches. Those theme relates to landscapes, environmental changes, site formation and human adaptation processes. Faunal ecofact and artifact are commonly used as research data nowdays. Analysis of plants residu are less common because of the scarcity of those remains in the archaeological sites,especially prehistory. This paper attempts to explain some possible uses of microscopic plant residua analysis in the form of phytolith and starch for environmental studies. The method used in this paper is literature study on microbotani as well as imitation experiments by combining several methods ever undertaken by previous researchers. This study shows that the plants remains , especially the microbotany form of phytolith and starch provide significant information about the types of plants in the pass, environmental changes and their utilization by humans.